Computation and Stability Analysis of Periodically Stationary Pulses in a Short Pulse Laser - Shinglot, Vrushaly; Zweck, John; Latushkin, Yuri; Menyuk, Curtis (My University, 2022)
A significant challenge in the modeling of short pulse fiber lasers is that with each successive generation there has been a dramatic increase in the amount by which the pulse varies over each round trip. Therefore, lumped rather than averaged models are required to accurately compute the periodically stationary (breather) solutions generated by these lasers.
Twelfth IMACS International Conference on Nonlinear Evolution Equations and Wave Phenomena: Computation and Theory, Athens, GA (Mar. 30 – Apr. 1, 2022)